Joint Beam Selection and Power Allocation for Multiple Target Tracking in Netted Colocated MIMO Radar System - Yan, Junkun; Liu, Hongwei; Pu, Wenqiang; Zhou, Shenghua; Liu, Zheng; Bao, Zheng (IEEE transactions on signal processing, 2016)
In this paper, a joint beam selection and power allocation (JBSPA) strategy is developed for multiple target tracking in netted colocated multiple-input multiple-output radar system. Each radar in this network adopts a multibeam working mode, in which multiple simultaneous transmit beams are synthesized. The basis of the JBSPA strategy is to use the optimization technique to control the limited beam and power resource of each radar in order to achieve accurate target state estimation. The Bayesian Cramér-Rao lower bound is derived, normalized, and subsequently utilized, as the optimization criterion for the JBSPA strategy. The resulting optimization problem consists of two adaptable parameters, one for beam selection and the other for power allocation. By introducing an auxiliary vector, a fast two-step solution technique is presented to jointly decide the number of beams generated by each radar, as well as the assignment and transmit power of each beam, subject to some resource constraints. Simulation results verify the superiority of the proposed JBSPA algorithm, in terms of the worst-case tracking accuracy of the multiple targets.